Systems (Holistic) Approach to Religious Tourism - Jere Jakulin, Tadeja (The international journal of religious tourism and pilgrimage, 2018)
Systems Approach has been accepted within natural sciences since Ludwig von Bertalanffy published his manifesto of general system theory (Bertalanffy, 1952) and Norbert Wiener his on Cybernetics (Wiener, 1948). The intention of general systems theory and cybernetics is the ontology' of action, which is shown by feedback information. Its goal is to find a method to predict the consequence of a decision-making action. Industrial engineering recognised it, when Forrester published the work Industrial Dynamics (Forrester, 1961) and social sciences rediscovered it with Senge's work on the learning organisation - The Fifth Discipline (Senge, 1990). Systems Approach is a methodology for complex phenomena research, theory and cybernetics, the disciplines, which play an important role in different fields of scientific research. Here we will present the tourism system from a systems point of view with special emphasis on religious tourism.